Pengalaman Pasien Hipertensi Primer Suku Minang yang Menjalani Perawatan di Rumah : Experiences of Minang Primary Hypertension Patients Undergoing Home Care - Rina; Setiawan; Cholina Trisna Siregar (NERS Jurnal Keperawatan, 2016)
Primary hypertension if not controlled properly at home will develop into secondary hypertension which may cause damage to the target organ. Primary hypertension is often called the "Silent Killer" because it has no early symptoms, patients often do not realize it and did not check into the health service thus increasing the incidence of hypertension, in general, increased prevalence of primary hypertension in West Sumatra province in which the majority of tribes Minang community. This study aims to dig deeper primary hypertension patients experience Minang tribe undergoing treatment at home. This type of research is descriptive phenomenology. The method used in this study using Colaizzi consisting of 7 steps. The number of participants in this study were 15 participants. Results of this study discusses the primary hypertension patients experience Minang tribe who undergo treatment at home. This study revealed six themes, namely; (1) Knowledge and understanding of hypertension, (2) Habit lived, the daily routine in the control of blood pressure at home, (3) feelings and beliefs on health, (4) barriers in controlling blood pressure at home, (5) external support in the control of blood pressure at home, and (6) reliance on the use of alternative therapies (naturally). Suggestions for patients with primary hypertension walking is a great exercise. This can be done each day, special training is not important, the important thing is regular exercise, regular physical activity can lower blood pressure by 5 to 10 mmHg.